Optimalisasi Pengelolaan Administrasi dan Layanan Perpustakaan Berbantuan Software : Optimalisasi Pengelolaan Administrasi dan Layanan Perpustakaan Berbantuan Software - Alwiyah, Alwiyah; Salamah, Umi (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2022)
The library is a source of information, a source of knowledge and education can be successful if its management is carried out properly and neatly. Among library management is administration and service management. In modern library management, administration and service management have used information technology as a means of automation in the form of hardware and software. The purpose of this research is to describe the administration of management and software-aided library services. The research approach used is qualitative with case study research as the type. The research instrument is the researcher. Data collection techniques used were observation, interviews and documentation. Data analysis techniques are data condensation, presentation and drawing conclusions. Checking the validity of the data uses a credibility technique (degree of trust) with data triangulation, a dependability technique and a confirmability technique. The results of this study, (1) library administration management consists of procurement of collections, classification of library materials, cataloging and labeling of library materials (2) management of library services consisting of circulation services, reference services and library rules. Optimization of management is done by automating the 3.0 library system software, making management work faster, time and energy efficiency.